TEACHERS’ BELIEFS AND PRACTICES IN ASSESSING THE VIEWING SKILL OF ESL LEARNERS - Gabinete, Mari Karen Lebumfacil (Indonesian Journal of Applied Linguistics, 2017)
This study explored the English/Language Arts teachers’ beliefs and practices in teaching and assessing students’ viewing skills in secondary education in the Philippines. Three secondary teachers in three government-run institutions were surveyed, interviewed and observed regarding their conception of visual literacy. The study revealed that teacher belief is influenced by their early education. In addition, teachers’ ability to teach and assess viewing skills relies not only on teacher training but also on access to technology and availability instrutional materials.  The study suggests a call to strengthen school or government support in order to promote viewing comprehension in basic education to meet the demands of the 21st century.